"Where the Shoe Pinches”: Impediments to Successful Execution of Gender Quota Thresholds in Kenya - KILELO, HELLEN (Advances in Social Sciences Research Journal, 2019)
The promulgation of the 2010 Kenyan Constitution inspired me to carry out a research with the objective of identifying the impediments to the successful implementation of gender quotas. This study was carried out in the year 2018 after the second set of County Governments had settled in office. Specifically, I adopted a multiple case study design because I examined perspectives on the implementation of the gender quota threshold in two cases i.e. two Counties. Purposive sampling was used to arrive at the participants. Data for this research was generated using interviews, Focus Group Discussions, and document analysis and the data collected was analyzed thematically. The interviews were conducted with County Public Officers, MCAs and other stakeholders purposively selected in the two Counties and key stakeholders in Nairobi. The main findings to this study were as follows: recruitment mechanisms are riddled with male patronage and bias; there are structural barriers and exclusionary practices that deter successful implementation of gender quotas; there is limited funding for Gender Departments and Gender Committees in the Counties and there are social perceptions that hinder the effectiveness of the gender quota threshold. In conclusion, gender quotas require a perceptual shift. The following recommendations are given in this study: there is need to have incentives that will help promote gender quota thresholds, the need to have a sectoral approach to gender and a strategy for balancing between quantity and quality.